Rational inattention and the business cycle effects of productivity and news shocks - Bartosz Maćkowiak; Mirko Wiederholt (European Central Bank (ECB), 2023)
We solve a real business cycle model with rational inattention (an RI-RBC model). In the RI-RBC model, the growth rates of employment, investment, and output are about as persistent as in the data, with an amount of inattention consistent with survey data on expectations. Moreover, consumption, employment, and output move in the same direction in response to news about future productivity. By contrast, the baseline RBC model produces neither persistent growth rates nor business cycle comovement after news shocks.
Keywords: D83; E32; E71; 330; information choice; rational inattention; real business cycle model; productivity shocks; news shocks